ICT in the SMEs of the 21st Century: Problems, adoption and training needs in ICT (2020)
in this book, we present an epistemic and legal configuration of the notion of small and medium enterprises (SMEs): we conceptualize it and define its importance in the field of national and international legislation. at the same time, we present the genesis of the use of information and communication technologies (ICT) in SMEs and describe the kinds of technology (software and hardware), to show the role these technologies have been played in the development of this type of enterprise, as well as the problems that arise in the third millennium. Finally, we make an assessment on the way in which ICTs have been adapted for SMEs, from their access, use, and adoption, with the aim of making a diagnosis of the training needs of SMEs in Santa Marta. one of the conclusions of this study is that many of the SMEs believe that ICTs are not necessary for their commercial activity or that their acquisition and maintenance is expensive. Therefore, we need to design a dissemination program to bring more information about the importance of these tools for business development, increasing the productivity and competitiveness of the company. ICT enable business objectives to be achieved more effectively because they improve access to information, support administrative management, expand access to suppliers and customers, and facilitate the promotion of products, both locally and globally.